Refine Frame Work on Cyber-physical System in Automatic Harvesting - Pandey, Khushi; Chudasama, Dhaval (E-COMMERCE FOR FUTURE & TRENDS, 2022)
India’s economy is heavily reliant on agriculture, which is currently one of the world’s top two producers. Roughly, 52% of all jobs in India are provided by this industry, which also contributes about 18.1% of the country’s GDP (gross domestic product). A significant issue in Asia is the fall in the number of farmers and labourers owing to a variety of circumstances, which results in higher labour costs and inefficient energy harvesting. Researchers are working to develop practical, affordable, and simple solutions that can replace machinery and agricultural automation in the long run to address these problems. This study examines several design approaches used in fruit picking and recognition technologies, and how these technologies have changed over the past 30 years in various countries. The use of harvesting robots offers a way to lower labour expenses, enhance production planning, permit selective harvests, and boost work productivity. Users of robotic harvesters can increase production and profitability by developing these capabilities. As an illustration of the most current developments in intelligent robots for automatic agricultural harvesting, this article examines the automated systems for harvesting fruits like peppers, tomatoes, apples, and kiwifruit. A summary of current techniques for choosing harvesting robots from the various production techniques includes an open area, a conservatory, and an orchard. Discussions about the restrictions of today’s systems recommend the creation of future research.